Nutrient release from litter by rains in a cacao agrosystem of south Bahia - Rodrigues, Antonio Carlos da Gama; de Miranda, Ricardo Augusto C. (Pesquisa Agropecuaria Brasileira, 1991)
The extraction of nutrients from litter by rains was evaluated in a plot of cocoa (Theobroma cacao L. cv. Catongo) partially shadowed by Erythrina fusca in a Typic tropudalf soil. There was some seasonality in the liberation of Ca, Mg, K, P e Cu. All year long there was no release of certain nutrients as N, Na and Zn. The large net increments in kg . ha-1 . year-1 were those of Mg and K.